Team based learning in pathology: Lessons learned from a pilot study - Bhargava Shruti (Medical Society of the Republic of Srpska, Banja Luka, University of Banja Luka. Faculty of Medicine, 2021)
Background: Team based learning (TBL) is an approach where students are organised in groups where they learn from each other. TBL is a student centric approach, which ensures active participation of each member and also promotes teamwork and learning ability. Looking at the teacher centric approach of the conventional teaching learning methods in medical education, where the students are mere passive learners and the sessions can be monotonous, TBL seems to be extremely relevant today as a more student centric teaching learning method. Aim of this study was to compare TBL with conventional teaching learning method (CTL). Methods: This randomised crossover study was conducted in the Department of Pathology, SMS Medical College, on 224 third semester medical students, wherein they were exposed to TBL session and their learning outcome and perception was compared to CTL. The data was analysed using Primer version 6 software. Results: In this study, there was a statistically significant improvement (p < 0.001) in the score of students after exposure to TBL. Also, there was a significant difference in the learning outcome of students of TBL (mean assessment score 7.21) as compared to CTL (mean assessment score 6.09). The student perception trends revealed a positive tilt towards TBL, wherein 70.98 % students agreed that TBL was a better learning strategy as compared to lectures. Conclusion: This pilot study concluded that TBL can be used as a supplement to the conventional lectures for improving the learning as well as team work and leadership skills of students.